Military internal security operations in Plateau State, North Central Nigeria : Ameliorating or exacerbating insecurity? - Musa, Sallek Yaks (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.